Bacterial Outer Membrane Vesicles and Vaccine Applications - Acevedo, Reinaldo; Fernandez, Sonsire; Zayas, Caridad; Acosta, Armando; Sarmiento, Maria E.; Ferro, Valerie A.; Rosenqvist, Einar; Campa, Concepcion; Cardoso, Daniel; Garcia, Luis; Perez, Jose L. (Frontiers in Immunology, 2014)
Vaccines based on outer membrane vesicles (OMV) were developed more than 20 years ago against Neisseria meningitidis serogroup B. These nano-sized structures exhibit remarkable potential for immunomodulation of immune responses and delivery of “self” meningococcal antigens or unrelated antigens incorporated into the vesicle structure. This paper reviews different applications in OMV Research and Development (R&D) and provides examples of OMV developed and evaluated at the Finlay Institute in Cuba. A Good Manufacturing Practice (GMP) process was developed at the Finlay Institute to produce OMV from N. meningitidis serogroup B (dOMVB) using detergent extraction. Subsequently, OMV from N. meningitidis, serogroup A (dOMVA), serogroup W (dOMVW) and serogroup X (dOMVX) were obtained using this process. More recently, the extraction process has also been applied effectively for obtaining OMV on a research scale from Vibrio cholerae (dOMVC), Bordetella pertussis (dOMVBP), Mycobacterium smegmatis (dOMVSM) and BCG (dOMVBCG). The immunogenicity of the OMV have been evaluated for specific antibody induction, and together with functional bactericidal and challenge assays in mice have shown their protective potential. dOMVB has been evaluated with non-self neisserial antigens, including with a herpes virus type 2 glycoprotein, ovalbumin and allergens. In conclusion, OMV are proving to be more versatile than first conceived and remain an important technology for development of vaccine candidates.